2017
DOI: 10.1111/age.12547
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping by sequencing reveals a new locus for pig teat number

Abstract: Teat number is an extremely valuable trait for sow reproduction performance and piglet survival. Here, we used genotyping-by-sequencing and a general liner model to carry out genome-wide analysis of sow total teat number in an Erhualian population. The results indicated that eight SNPs on chromosomes 4, 5, 9 and 10 were significant genome wide (Bonferroni method, P < 2.85E-7) for sow total teat number. Validation analyses were performed in 298 Erhualian and 904 Large White sows using these significant SNPs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…Genotype marker density is one important factor affecting the efficiency of GWAS (Brondum et al, 2012).With the increase of marker density, the linkage disequilibrium between markers and the target trait QTL is increased, which is helpful for QTL detection. In previous studies, the advantages of whole genome sequencing data have been demonstrated (Wang L. et al, 2017). However, its high cost hampered the wide application of sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype marker density is one important factor affecting the efficiency of GWAS (Brondum et al, 2012).With the increase of marker density, the linkage disequilibrium between markers and the target trait QTL is increased, which is helpful for QTL detection. In previous studies, the advantages of whole genome sequencing data have been demonstrated (Wang L. et al, 2017). However, its high cost hampered the wide application of sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have been widely used to analyze the genetic architecture of reproduction, meat quality, and production traits in the pig population ( Verardo et al, 2016 ; Schmid et al, 2018 ; Ding et al, 2019 ). Previous GWAS found that several single nucleotide polymorphisms (SNPs) in or near the bone morphogenetic protein 2 ( BMP2 ) gene were associated with body length and body height, and many reported that the vertebrae development-associated ( VRTN ) gene was significantly associated with total teat number in pigs ( Lee et al, 2014 , 2019 ; Arakawa et al, 2015 ; Wang et al, 2017 ). Almost all GWAS for body length, body height, and total teat number were performed by single-locus GWAS.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, GWAS has been widely used to identify quantitative trait loci (QTL) and quantitative trait nucleotides (QTN) in important quantitative traits, such as teat number (48), growth traits (37), and meat traits (28). Reproductive traits are among the important economic traits in pig breeding.…”
Section: Introductionmentioning
confidence: 99%